Evaluación técnico-económico y ambiental de una alternativa para obtención de quitina y quitosano a partir de residuos de crustáceos en la EPICAI - Rojas Mayo, Zoila Rosa (Universidad Central ‘‘Marta Abreu’’ de Las Villas. Facultad de Química y Farmacia. Departamento de Ingeniería Química, 2021)
Las industrias procesadoras de pescado y mariscos (camarón, langosta, cangrejo, jaiba, entre otros) son altamente generadoras de desechos sólidos que contaminan el medio ambiente y se convierten en una carga económica para las mismas. Estos residuos son portadores de sustancias que tienen un alto valor agregado establecido a nivel mundial, como son, la quitina y el quitosano, ambos considerados como polímeros biofuncionales con amplia aplicación en el área de la biotecnología, en la medicina, la industria farmacéutica, la agricultura, entre otras. La transformación de estos residuos se puede realizar mediante tratamientos biológicos, químicos o la combinación de ellos, en dependencia de la aplicación y la industria a la que esté destinado el producto final. Este trabajo tiene como objetivo, proponer la implementación de una alternativa para la extracción de quitina a partir del exoesqueleto de crustáceos provenientes de la EPICAI, que sea factible desde el punto de vista técnico-económico y ambiental. Para dar solución a esto, se analizaron las diversas tecnologías para la obtención de este compuesto y se propuso la tecnología más apropiada para su producción, mediante el método químico.

The fish and shellfish processing industries (shrimp, lobster, crab, crab, among others) are highly generators of solid waste that pollute the environment and become an economic burden for them. These wastes are carriers of substances that have a high benefit established worldwide, such as chitin and chitosan, both considered as biofunctional polymers with wide application in the area of biotechnology, medicine, the pharmaceutical industry, and the agriculture, among others. The transformation of these wastes can be carried out by means of biological and chemical treatments or acombination of them, depending on the application and the industry for which the final product is destined. This work aims to propose the implementation of an alternative for the extraction of chitin from the exoskeleton of crustaceans from EPICAI, which is feasible from a technical-economic and environmental point of view. To solve this, the various technologies for obtaining this compound were analyzed and the most appropriate technology for its production was proposed, using the chemical method using phosphoric acid as a less harmful and cheaper alternative in the demineralization stage. Different production technologies were studied establishing the main stages of the process according to the necessary requirements of materials and supplies, being defined as fundamental stages, crushing, deproteinization, demineralization, deacetylation and drying. In addition, the necessary material and energy balances were carried out, as well as the sizing of the fundamental equipment of the proposed process. The pre-feasibility study of the project was carried out with the calculation of costs and dynamic indicators, resulting in that the process is economically feasible with a net present value (NPV) of $ 218081,3, an internal rate of return (IRR) 50% and a discounted payback period (PRD) of 2,7 years.
Keywords: Desechos de Crustáceos; Industria de Alimentos; Industria Pesquera; Procesamiento de Residuos Sólidos; Quitina/aislamiento & purificación; Quitosano/aislamiento & purificación